(untitled) (Social Science Review, 2022)
Ensuring human rights for Hijra is one of the prerequisites of a just society. The Hijras are perceived to live at risk of being the victims of social harassment everywhere due to negative societal attitudes towards this section. For this reason, they are far behind from the enjoyment of basic needs and fundamental rights that impede the realization of the human rights of Hijras. This article explores the reasons for the marginalization of the Hijra community and sheds light on how to ensure human rights in the prevailing legal structure of Bangladesh by overcoming the challenges. Consequently, this paper attempts to identify the effectiveness of the existing laws and policies to address the problem faced by hijras and thus find out the gaps. The author shows that leaving them far away from the mainstream society due to lack of implementation of existing laws, policies and lack of cordial attitude of the family as well as because of lacking in knowledge of hijras regarding the laws and policies. Mixed methods and snowball techniques have been applied to this study to collect and analyze the data. To this end, the author has stipulated some recommendations to sort out the problems and challenges. Social Science Review, Vol. 38(1), June 2021 Page 249-276